Solitary fibrous tumor of the chest wall with Doege–Potter syndrome: a case report - Zhang, Hongfei; Weng, Xinyue; Zhang, Yuqi; Wang, Yuchen; Liu, Jiangyue; Pang, Yutao; Li, Ang; Deng, Boyun; Li, Fasheng; Chen, Jie; Liang, Zhu; He, Zhan; et al. (Frontiers in Oncology, 2026)
ObjectiveTo describe the management of a rare chest wall solitary fibrous tumor (SFT) complicated by Doege–Potter syndrome (DPS), emphasizing the critical roles of multidisciplinary consultation and preoperative vascular embolization in optimizing outcomes.MethodsA 56-year-old male presented with exertional dyspnea, dizziness, recurrent hypoglycemia, and hypokalemia. Contrast-enhanced computed tomography (CT) identified a large chest wall mass (19.2 × 13.3 × 21.6 cm), with biopsy confirming SFT. Multidisciplinary evaluation established a diagnosis of DPS. The patient underwent three cycles of neoadjuvant chemo-immunotherapy (albumin-bound paclitaxel, cisplatin, and anlotinib), followed by preoperative tumor vascular embolization. Surgical intervention involved en bloc tumor resection, left upper lobe wedge resection, and partial resection of the fifth rib.ResultsNeoadjuvant therapy resulted in stable disease per RECIST 1.1 criteria. Preoperative embolization significantly reduced intraoperative blood loss to 200 mL, enabling an uneventful surgery. Postoperatively, hypoglycemia and hypokalemia resolved, and lung re-expansion was satisfactory. As of December 31, 2024, outpatient follow-up revealed no evidence of recurrence or metabolic abnormalities.ConclusionsThis case highlights the importance of recognizing DPS as a rare manifestation of chest wall SFT and underscores the value of multidisciplinary strategies in managing large tumors. Preoperative vascular embolization effectively minimized surgical risks and corrected metabolic disturbances, facilitating successful resection. Further studies are warranted to refine therapeutic approaches for this uncommon clinical entity.